2018
DOI: 10.1016/j.ijantimicag.2017.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of herpes simplex virus 1 (HSV-1) and poliovirus (PV-1) by bacteriocins from lactococcus lactis subsp. lactis and enterococcus durans strains isolated from goat milk

Abstract: Bacteriocins have unusual inhibitory activity, including antiviral properties, and this can be exploited to give alternative applications. Semi-purified bacteriocins of six lactic acid bacteria (LAB) strains isolated from goat milk (two Lactococcus lactis: GLc03 and GLc05, and four Enterococcus durans: GEn09, GEn12, GEn14 and GEn17) were tested for cytotoxicity in Vero cells (50% Cytotoxicity Concentration: CC), and for their antiviral activities against herpes simplex virus 1 (HVS-1) and poliovirus (PV-1). Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 38 publications
1
25
0
1
Order By: Relevance
“…Emergence of antibiotic resistance and growing consumer trend towards foods containing biopreservatives triggered the search for alternative antimicrobials and food preservatives [ 1 5 ]. Bacteriocins produced by lactic acid bacteria (LAB) are considered potential replacements or synergists to currently used antibiotics and chemical food preservatives [ 4 , 6 , 7 ]. LAB bacteriocins do not significantly change the microflora of the human gastrointestinal tract [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Emergence of antibiotic resistance and growing consumer trend towards foods containing biopreservatives triggered the search for alternative antimicrobials and food preservatives [ 1 5 ]. Bacteriocins produced by lactic acid bacteria (LAB) are considered potential replacements or synergists to currently used antibiotics and chemical food preservatives [ 4 , 6 , 7 ]. LAB bacteriocins do not significantly change the microflora of the human gastrointestinal tract [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the absence of cytotoxicity nisin is considered as safe (Jozala et al, 2007). Moreover, a low cytotoxicity was also reported for several other bacteriocins (Wachsman et al, 2003;Martinez et al, 2013;Carneiro et al, 2014;Quintana et al, 2014;Todorov et al, 2014;Cavicchioli et al, 2018). However, some report have referred to observations on potential cytotoxicity of some bacteriocins, and posed questions on their potential as health hazards (Carneiro et al, 2014;Kaur and Kaur, 2015).…”
Section: Bacteriocins and Control Ofmentioning
confidence: 99%
“…A period of 2–12 weeks for consumption of L. plantarum HEAL 9 and L. paracasei 8700 showed a reduction in the risk of acquiring common-cold infections caused by human rhinoviruses via induction of CD4 + and CD8 + cells [ 99 ]. Cavicchioli et al demonstrated that purified bacteriocins of L. lactis subspecies lactis had noticeable inhibitory activity against herpes poliovirus-1 [ 100 ]. Moreover, Nanis et al showed that administration of probiotics such as Lactobacillus acidophilus and Bifidobacteria species enhanced the healing response to treatments of infection by the hepatitis-C virus (HCV) by regulation of IFN-α and ribavirin [ 95 ].…”
Section: Characterisation and Potential Use Of Kefirmentioning
confidence: 99%
“…The HSV is the leading cause of herpes infection, which can develop in many parts of the body, but most frequently on the genitals (HSV-2) or mouth (HSV-1) [ 100 , [131] , [132] , [133] ]. L. lactis subspecies lactis, L. rhamnosus and L. brevis , and L. crispatus have activity against HSV-1 and HSV-2, respectively [ 100 ]. A recent study revealed that purified bacteriocins of L. lactis subspecies lactis had noticeable inhibitory activity against HSV-1 and could be used as new antiviral agents [ 100 ].…”
Section: Characterisation and Potential Use Of Kefirmentioning
confidence: 99%